The intervention of (Latin) American international law: united states hegemony and the debate over intervention in the origins of the Inter-American system (Estudios Sociales, 2020)
This article examines the debates generated over the conformation of international law, the nature of the Monroe Doctrine and the principle of intervention in the context of the rise of the United States as an informal empire in Latin America and the formation of the Inter-American System. It argues that this process contributed to the formation of three opposing legal traditions in the region that emerged alongside US hegemony and interventionism.
Keywords: International Law; Latin America; Intervention; United States; Inter-American System